Criterial feature-level activation of the educational-cognitive activity of students in the process of working with dictionaries (Pedagogy of Higher and Secondary Education, 2012)
Kirikilitsa V. Criterial feature-level activation of the educational-cognitive activity of students in the process of working with dictionaries.The article is devoted to theoretical grounding of criteria and indices of students’ knowledge and cognitive activities activation during dictionary activity, also levels of their formation are analyzed.
Keywords: criteria; indices; levels; activation; knowledge and cognitive activities; dictionary activity